Characterization of the peridinin–chlorophyll a-protein complex in the dinoflagellate Symbiodinium - Jiang, Jing (2012)
The water-soluble peridinin–chlorophyll a-proteins (PCPs) are one of the major light harvesting complexes in photosynthetic dinoflagellates. PCP contains the carotenoid peridinin as its primary pigment. In this study, we identified and characterized the PCP protein and the PCP gene organization in Symbiodinium sp. CS-156. The protein molecular mass is 32.7 kDa, revealing that the PCP is of the monomeric form. The intronless PCP genes are organized in tandem arrays. The PCP gene cassette is composed of 1095-bp coding regions and spacers in between. Despite the heterogeneity of PCP gene tandem repeats, we identified a single form of PCP, the sequence of which exactly matches the deduced sequence of PCP gene clone 7 (JQ395030) by LC–MS/MS analysis of tryptic digested PCP, revealing the mature PCP apoprotein is 312 amino acids in length. Pigment analysis showed a peridinin-to-Chl a ratio of 4. The peridinin-to-Chl a Q(y) energy transfer efficiency is 95% in this complex.